DC Bus Control of Back-to-Back Connected Two-Level PWM Rectifier-Five-Level NPC Voltage Source Inverter to Torque Ripple Reduction in Induction Motor - Abdelkrim, Thameur; Benamrane, Karima; Bezza, Badreddine (MATEC web of conferences, 2015)
This paper proposes a regulation method of back-to-back connected two-level PWM rectifier-five-level Voltage Source Inverter (VSI) in order to reduce the torque ripple in induction motor. First part is dedicated to the presentation of the feedback control of two-level PWM rectifier. In the second part, five-level Neutral Point Clamped (NPC) voltage source inverter balancing DC bus algorithm is presented. A theoretical analysis with a complete simulation of the system is presented to prove the excellent performance of the proposed technique.